EVALUASI WEBSITE PERPUSTAKAAN UNIVERSITAS UDAYANA - Widiantara, I Nyoman; Widiantara, I Nyoman; Suhartika, I Putu; Nugraha, A.A Bagus Surya Widya (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 1 No 1 (2021), 2021)
ABSTRACT   The purpose of this study was to evaluate Website the Udayana University Library using the webqual 3.0 method. The method used in this research is a descriptive quantitative method. The population in this study were visitors to the Udayana University Library on April 26, 2021 to May 3, totaling 151 students. The number of samples in this study was determined using the Slovin formula, counted as many as 60 students. The sampling technique was accidental sampling, namely by distributing questionnaires to Udayana University students who were in the Udayana University Library and had used the website Udayana University Library. There are three aspects of the Webqual 3.0 method that are used as a reference, namely the evaluation of the aspects of user convenience, information quality, and interaction service quality. With this, the three aspects are expected to improve the quality of the Udayana University Library website   Keywords: Webqual 3.0, website, Udayana University Library